2017
DOI: 10.1590/1518-8345.1640.2889
|View full text |Cite
|
Sign up to set email alerts
|

Organization of professional practices against intrafamily violence against children and adolescents in the institutional context

Abstract: Objective:to analyze based on the practitioners' discourse, the way they organize their practices confronting situations of intra-family violence against children and adolescents. Method:qualitative research carried out with 15 professionals who work in social and health services located in the southernmost of Brazil. Data were collected through semi-structured interviews, performed at the participants' workplace. We used a theoretical matrix to analyze the data, based on Institutional Ethnography and the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 11 publications
0
10
0
16
Order By: Relevance
“…O Conselho Tutelar é o órgão público encarregado de zelar pelo cumprimento dos direitos das crianças e dos adolescentes a partir da aplicação de medidas de proteção, atendimento e aconselhamento de pais ou responsáveis, requisição de serviços e realização de encaminhamentos à rede de referência (11). No entanto, vale ressaltar as dificuldades que esse órgão vem enfrentando, conforme demonstrou estudo realizado em Minas Gerais ao evidenciar limitações como: ausência de formação continuada para o exercício da função, ações pautadas segundo preceitos e convicções pessoais, excesso de burocracia no andamento dos casos e falta de estrutura física adequada (12).…”
Section: Discussionunclassified
“…O Conselho Tutelar é o órgão público encarregado de zelar pelo cumprimento dos direitos das crianças e dos adolescentes a partir da aplicação de medidas de proteção, atendimento e aconselhamento de pais ou responsáveis, requisição de serviços e realização de encaminhamentos à rede de referência (11). No entanto, vale ressaltar as dificuldades que esse órgão vem enfrentando, conforme demonstrou estudo realizado em Minas Gerais ao evidenciar limitações como: ausência de formação continuada para o exercício da função, ações pautadas segundo preceitos e convicções pessoais, excesso de burocracia no andamento dos casos e falta de estrutura física adequada (12).…”
Section: Discussionunclassified
“…Also, only users speak of institutional violence and express dissatisfaction with the inadequacy of physical space, lack of privacy, impersonality as explicit forms and that cause more violence. Moreover, as Schek et al 18 mention, the high demand for care may contribute to the insufficient registration of suspected or confirmed cases that require more time to approach.…”
Section: Violence As a Health Problemmentioning
confidence: 99%
“…22 With regard to the network of care for children in situations of violence, a study found that there are concerns in the professionals' speeches in terms of supply and demand in relation to social services and health care in children, and the professionals have a responsibility to strengthen shared actions, establishing an effective protection network that includes referral and counterreferral services capable of acting on the multiple demands for attention and care expressed by children and families in situations of violence. 23 Thus, there is the need to articulate, in the field of nursing, the theoretical and practical knowledge aiming to build learning of the future professionals in the development of their potentialities in the service and application of the professional autonomy of the nurse. 24 Nursing students showed lack of knowledge in the identification of children in situations of domestic violence, since they presented a view focused on the biomedical model, valuing the clinical signs, highlighting the marks left in the child's body after the physical aggression as a form of identification domestic violence; also, that there are behavioral aspects that need to be taken into account in the child, which may indicate a situation of violence, even without obvious physical aggression, such as agitation, aggression, bad mood and difficulty in socializing with other children.…”
Section: -21mentioning
confidence: 99%